In silico evaluation of the Eucalyptus transcriptome - Vicentini, Renato; Sassaki, Flávio T. [UNESP]; Gimenes, Marcos A. [UNESP]; Maia, Ivan de Godoy [UNESP]; Menossi, Marcelo (FapUNIFESP (SciELO), 2005)
The expressed sequence tags (ESTs) produced in the Forests project provide an invaluable opportunity to assess the Eucalyptus transcriptome. Besides providing information on the different proteins produced by this plant, it is possible to infer gene expression profiles because non-normalized cDNA libraries were used. The EST frequency from any gene is correlated to the transcript levels in the tissues from which the cDNA libraries were constructed. The goal of this work was to identify Eucalyptus genes that showed either differential expression pattern or were ubiquitously expressed in the tissues sampled in the Forests project. Six robust statistical tests and very restrictive rules were applied to gain confidence in the in silico data aiming to avoid false positives. Several genes with interesting expression profiles were identified and some of them were validated by RT-PCR. Copyright by the Brazilian Society of Genetics.
Keywords: Differential expression; Eucalyptus; Statistics; Tissue-specific; Transcriptome; transcriptome; computer model; controlled study; gene expression profiling; genetic database; genetic identification; genetic selection; nonhuman; plant genetics; plant tissue; reverse transcription polymerase chain reaction; statistical analysis; validation process